Poly(neutral red) based hydrogen peroxide biosensor for chromium determination by inhibition measurements - Attar, Aisha (2014)
Amperometric hydrogen peroxide enzyme inhibition biosensors based on horseradish peroxidase (HRP) immobilised on electropolymerised neutral red (NR) or directly on the surface of carbon film electrodes (CFE) have been successfully applied to the determination of toxic Cr(III) and Cr(VI). Parameters influencing the performance of the biosensor including the enzyme immobilisation method, the amount of hydrogen peroxide, applied potential and electrolyte pH were optimised. The inhibition of horseradish peroxidase by the chromium species was studied under the optimised conditions. Results from the quantitative analysis of chromium ions are discussed in terms of detection limit, linear range and sensitivity. The HRP kinetic interactions reveal mixed binding of Cr(III) with I50 = 3.8 μM and inhibition binding constant Ki = 11.3 μM at HRP/PNR/CFE biosensors and uncompetitive binding of Cr(VI) with I50 = 3.9 μM and Ki = 0.78 μM at HRP/CFE biosensors in the presence of H2O2 substrate. Interferences from other heavy metal ions were studied and the inhibition show very good selectivity towards Cr(III) and Cr(VI).